Bodily Engagements with Film, Images and Technology: Somavision - A Book Review - Aurosa Alison (ESPES, 2025)
Book review of Ryynänen, M.: (2022) Bodily Engagements with Film, Images and Technology. Somavision. New York – London: Routledge.